(untitled) (International journal of artificial intelligence, 2025)
Listening comprehension is a key element of foreign language learning, as it provides learners with essential linguistic input. Using audio and video materials in instruction greatly supports the development of listening skills by offering authentic and engaging content. Audio exposes learners to natural speech, pronunciation, rhythm, and intonation, while video adds visual cues such as gestures and situational context that make understanding easier. These multimodal resources enhance both bottom-up and top-down processing, boost motivation, promote cultural awareness, and support autonomous learning. When used effectively, audio and video materials become powerful tools that strengthen listening proficiency and enrich the overall language learning experience.